The matter of spatial and temporal scales: a review of reindeer and caribou response to human activity - Vistnes, Ingunn; Nellemann, Christian (2008)
Research on impacts of human activity and infrastructure development on reindeer and caribou (Rangifer tarandus) is reviewed in the context of spatial (m to many km) and temporal (min to decades) scales.